2016
DOI: 10.1002/esp.3913
|View full text |Cite
|
Sign up to set email alerts
|

Morphology, structure and kinematics of a rainfall controlled slow‐moving Andean landslide, Peru

Abstract: The large slow‐moving landslide of Maca is located in the upper Colca valley (southern Peru), a region characterized by a well pronounced rainy period, and intense and recurrent sustained seismicity. The landslide, developed in deep lacustrine deposits, has recently accelerated, threatening the Maca village. This work aims at understanding the rupture mechanism and the causes of the recent landslide reactivation/acceleration. We present a multidisciplinary characterization of the Maca landslide that includes: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 55 publications
1
33
0
Order By: Relevance
“…1 and Supplementary Fig. 1) has been identified has a clay/silt compound slide with a rupture surface of uneven curvature 24 and thus, belongs to the soil slide category 25 . This 60 million m 3 landslide impacts a village in a rural area in the Colca Valley, southern Peru, in a very seismically active zone 26,27 .…”
Section: Resultsmentioning
confidence: 99%
“…1 and Supplementary Fig. 1) has been identified has a clay/silt compound slide with a rupture surface of uneven curvature 24 and thus, belongs to the soil slide category 25 . This 60 million m 3 landslide impacts a village in a rural area in the Colca Valley, southern Peru, in a very seismically active zone 26,27 .…”
Section: Resultsmentioning
confidence: 99%
“…As a consequence, the study of slow-moving landslides may lead a better understanding of the physical processes governing both slow and rapid landslides (Palmer, 2017). In recent years, various studies of slow-moving landslides (e.g., Bennett et al, 2016;Handwerger et al, 2013Handwerger et al, , 2015Hsu et al, 2014;Iverson & Major, 1987;Lacroix et al, 2014Lacroix et al, , 2015Reid, 1994;Schulz et al, 2009;Zerathe et al, 2016) have revealed a rich diversity in kinematics, with various forcing factors, for example, rainfall, earthquakes, glacial retreat, and anthropogenic activity. These forcings act over a wide variety of timescales, from seconds (earthquakes Lacroix et al, 2014) to several decades (glacial retreat Strozzi et al, 2010), thus making their study challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Landslide motion is often interpreted to occur as a direct consequence of external forcing factors (e.g., Handwerger et al, 2013Handwerger et al, , 2015Hsu et al, 2014;Lacroix et al, 2014;Reid, 1994;Zerathe et al, 2016), such as rainfall or ground shaking (i.e., from earthquakes). However, different internal processes may also influence landslide motion; for example, progressive failure is thought to play a key role in the initiation of landslide motion (Amitrano, 2004;Carey & Petley, 2014;Eberhardt et al, 2004;Gischig et al, 2016;Lacroix & Amitrano, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…One obvious reason is an applied normal stress much lower than for tectonic faults or laboratory experiments (typically of the order of 10–100 MPa) so that very few contacts reach the plastic limit, an effect enhanced for smoother surfaces. This would be consistent with the fact that the interface of the Maca landslide studied in [ Lacroix et al , ] is about 70 m below the surface [ Zerathe et al , ]. Assuming a rock density of 3000 kg/m 3 , this corresponds to a lithostatic pressure of about 2 MPa, 1 or 2 orders of magnitude lower than typical normal stress in laboratory experiments.…”
Section: Discussionmentioning
confidence: 99%